The association between treatment adherence to nicotine patches and smoking cessation in pregnancy: A secondary analysis of a randomized controlled trial - Vaz, L; Aveyard, P; Cooper, S; Leonardi-Bee, J; Coleman, T (Oxford University Press, 2016)
In nonpregnant "quitters," adherence to nicotine replacement therapy (NRT) increases smoking cessation. We investigated relationships between adherence to placebo or NRT patches and cessation in pregnancy, including an assessment of reverse causation and whether any adherence: cessation relationship is moderated when using nicotine or placebo patches.Using data from 1050 pregnant trial participants, regression models investigated associations between maternal characteristics, adherence and smoking cessation.Adherence during the first month was associated with lower baseline cotinine concentrations (β -0.08, 95% confidence interval [CI] -0.15 to -0.01) and randomization to NRT (β 2.59, 95% CI 1.50 to 3.68). Adherence during both treatment months was associated with being randomized to NRT (β 0.51, 95% CI 0.29 to 0.72) and inversely associated with higher nicotine dependence. Adherence with either NRT or placebo was associated with cessation at 1 month (odds ratio [OR] 1.11, 95% CI 1.08 to 1.13) and delivery (OR 1.06, 95% CI 1.03 to 1.09), but no such association was observed in the subgroup where reverse causation was not possible. Amongst all women, greater adherence to nicotine patches was associated with increased cessation (OR 2.47, 95% CI 1.32 to 4.63) but greater adherence to placebo was not (OR 0.98, 95% CI: 0.44 to 2.18).Women who were more adherent to NRT were more likely to achieve abstinence; more nicotine dependent women probably showed lower adherence to NRT because they relapsed to smoking more quickly. The interaction between nicotine-containing patches and adherence for cessation suggests that the association between adherence with nicotine patches and cessation may be partly causal.This study used placebo randomized controlled trial data to investigate both associations between women's characteristics and adherence to NRT patch treatment, and the relationship between adherence to NRT patch treatment and odds of cessation in pregnant quitters. Greater adherence was seen with NRT patches, and greater adherence with NRT patches increased the odds of smoking cessation. A likely explanation for findings is that NRT patches, if used sufficiently, may be effective for at least some pregnant women who try to stop smoking. Trials testing interventions which encourage women's adherence to higher dose NRT are indicated.